2016
DOI: 10.1111/1462-2920.13538
|View full text |Cite
|
Sign up to set email alerts
|

Water mass mixing shapes bacterial biogeography in a highly hydrodynamic region of the Southern Ocean

Abstract: Even though compelling evidences indicate that marine microbes show biogeographic patterns, very little is known on the mechanisms driving those patterns in aquatic ecosystems. In the present study, bacterial community structure was examined in epipelagic waters of a highly hydrodynamic area of the Southern Ocean to gain insight into the role that biogeochemical factors and water mass mixing (a proxy of dispersal) have on microbial biogeography. Four water masses that converge and mix around the South Shetland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 69 publications
3
20
1
Order By: Relevance
“…In this study, we showed that even under at the same scale, the spatial effect can change through time, depending on the strength of stratification. These findings are in line with the notion that the geographic distance per se may not serve as a good proxy for dispersal limitation (Lindstrom and Langenheder, 2012); rather, hydrographic processes such as the connectivity between water masses would play a key role in mediating dispersal of bacteria (Galand et al, 2010;Hernando-Morales et al, 2017).…”
Section: Mechanism Shaping Vertical Beta Diversity Varied Depending Osupporting
confidence: 85%
“…In this study, we showed that even under at the same scale, the spatial effect can change through time, depending on the strength of stratification. These findings are in line with the notion that the geographic distance per se may not serve as a good proxy for dispersal limitation (Lindstrom and Langenheder, 2012); rather, hydrographic processes such as the connectivity between water masses would play a key role in mediating dispersal of bacteria (Galand et al, 2010;Hernando-Morales et al, 2017).…”
Section: Mechanism Shaping Vertical Beta Diversity Varied Depending Osupporting
confidence: 85%
“…Moreover, wind patterns and weather conditions may also be included in statistical models, since there are several studies that have shown the potential of long distance transport of viable microorganisms on dust particles (e.g., de la Campa et al ., ; Choudoir et al ., ). Other examples are the ocean water mass mixing index (Hernando‐Morales et al ., ) and hydrological connectivity among lakes and streams (Niño‐Garcia et al ., ) as well as groundwater sites (Freimann et al ., ) that show a closer connection to aquatic microbial community composition than geographic distance. Water retention time might also be specifically used as a tool to predict under which circumstances mass effects are likely to occur in plankton communities (Lindström et al ., ; Niño‐Garcia et al ., ).…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 99%
“…Recent biogeography research has demonstrated microbial diversity patterns are detectable and are influenced by both deterministic 33 and stochastic processes 6 . A lack of consensus on the relative impact of these factors, however, has been exacerbated by an absence of broad physicochemical gradients, and sampling scale and density across both geographic distance and habitat type.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies, however, have contradicted this paradigm and shown that microbial community diversity is shaped across time and space 2,3 via a combination of environmental selection, stochastic drift, diversification and dispersal limitation 4,5 . The relative impact of these ecological drivers on diversity is the subject of ongoing debate, with differential findings reported across terrestrial, marine and human ecosystems 6-12 .…”
mentioning
confidence: 99%